적외선 체온의 진단 정확도 평가 연구: 체계적 문헌고찰 - 박성희(Park, Seong-Hi) (Sŏngin Kanho Hakhoe chi, 2014)
Purpose: The aim of this study was to investigate the accuracy of infrared temperature measurements compared to axillary temperature in order to detect fever in patients. Methods: Studies published between 1946 and 2012 from periodicals indexed in Ovid Medline, Embase, CINAHL, Cochrane, KoreaMed, NDSL, KERIS and other databases were selected using the following key words: "infrared thermometer". QUADAS-II was utilized to assess the internal validity of the diagnostic studies. Selected studies were analyzed through a meta-analysis using MetaDisc 1.4. Results: Twenty-one diagnostic studies with high methodological quality were included representing 3,623 subjects in total. Results of the meta-analysis showed that the pooled sensitivity, specificity, and area under the curve (AUC) of infrared tympanic thermometers were 0.73 (95% CI 0.70~0.75), 0.92 (95% CI 0.91~0.92), and 0.90, respectively. For axillary temperature readings, the pooled sensitivity was 0.67 (95% CI 0.62~0.73), the pooled specificity was 0.87 (95% CI 0.85~0.90), and the AUC was 0.80. Conclusion: Infrared tympanic temperature can predict axillary temperature in normothermic and in febrile patients with an acceptable level of diagnostic accuracy. However, further research is necessary to substantiate this finding in patients with hyperthermia.